Second‐trimester growth velocities in twin and singleton pregnancies. (3rd January 2023) - Anderson, J. N.; Deter, R. L.; Datoc, I. A.; Mack, L.; Gandhi, M.; Lee, W.; Blumenfeld, Y. J.
ABSTRACT: Objective: Previous small studies used individualized growth assessment (IGA) to characterize prenatal growth velocities of singletons and twins. We aimed to compare second‐trimester growth velocities of individual anatomical parameters between monochorionic diamniotic (MCDA) twins, dichorionic diamniotic (DCDA) twins and singleton fetuses in a larger study. Methods: This was a study of a novel cohort of 222 MCDA twins and previously published cohorts of 40 DCDA twins and 118 singletons with serial ultrasound data. Fetal biometric measurements of biparietal diameter, head circumference, abdominal circumference and femur diaphysis length from prenatal ultrasound examinations were used to calculate second‐trimester growth velocities using direct calculation or linear regression analysis. Linear fit was assessed based on the coefficient of determination ( R 2 ). Mean growth velocities and variances were compared among the three groups. Results: The majority of cases underwent three second‐trimester ultrasound examinations with fetal biometry available. All fetuses had linear growth, with R 2 > 99% for all parameters. Only 1–2% of all MCDA and DCDA anatomical parameters had abnormal growth velocity scores outside the 95% reference range for singletons. There were no significant differences in mean growth velocity for any parameter between MCDA twins and singletons. Femur diaphysis length growth velocity was significantly lower in DCDA twins than in both MCDA twins and singletons. There were no other significant differences among the groups. Conclusions: Expanding on prior work using IGA, we found that second‐trimester growth velocity of the four major anatomical parameters overall was similar between twins and singletons and between MCDA and DCDA twins, supporting the use of singleton‐derived growth standards for IGA in twins. Twin growth potential appears to be similar to that of singletons in the second trimester, suggesting that subsequent growth divergence may be due to third‐trimester physiological or pathological changes in twin pregnancies. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.